An integrated nanocatalyst combining enzymatic and metal–organic framework catalysts for cascade degradation of organophosphate nerve agents. Issue 76 (7th September 2018) - Li, Haibin; Ma, Li; Zhou, Liya; Gao, Jing; Huang, Zhihong; He, Ying; Jiang, Yanjun
Abstract : An integrated nanocatalyst that combined a metal–organic framework-based catalyst and a biocatalyst was developed for cascade degradation of organophosphate nerve agents. Abstract : An integrated nanocatalyst (INC), denoted OPH@MIL-100(Fe), was synthesized by immobilizing a biocatalyst onto a metal–organic framework (MOF)-based catalyst, which can cascadingly degrade organophosphate nerve agents to 4-aminophenol (4-AP) and result in a sharp decrease of their toxicity up to 208-fold.